OpenCIn: Usando Dados Abertos e Conectados para a Publicação de dados sobre o CIn/UFPE - Rocha, Jônatas; Lóscio, Bernadette (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2015)
In general, the currently available information on the Web is produced to be comprehended by humans and not by machines, bringing difficulties both for extraction and for processing such information by computers. In this context, the Semantic Web has been proposed as a solution to facilitate the sharing and processing of data available on the Web because it makes the information readable by machines adding meaning to Web documents. This work aims to create an environment that facilitates access and manipulation of information about the teachers at Centro de Informática - UFPE, using the technologies that the Semantic Web proposes.